Optimal Antithrombin Activity Threshold for Initiating Antithrombin Supplementation in Patients With Sepsis-Induced Disseminated Intravascular Coagulation: A Multicenter Retrospective Observational Study - Hayakawa, Mineji (Clin Appl Thromb Hemost, 2018)
Low-dose antithrombin supplementation therapy (1500 IU/d for 3 days) improves outcomes in patients with sepsis-induced disseminated intravascular coagulation (DIC). This retrospective study evaluated the optimal antithrombin activity threshold to initiate supplementation, and the effects of supplementation therapy in 1033 patients with sepsis-induced DIC whose antithrombin activity levels were measured upon admission to 42 intensive care units across Japan. Of the 509 patients who had received antithrombin supplementation therapy, in-hospital mortality was significantly reduced only in patients with very low antithrombin activity (≤43%; bottom quartile; adjusted hazard ratio: 0.603; 95% confidence interval: 0.368-0.988; P = .045). Similar associations were not observed in patients with low, moderate, or normal antithrombin activity levels. Supplementation therapy did not correlate with the incidence of bleeding requiring transfusion. The adjusted hazard ratios for in-hospital mortality increased gradually with antithrombin activity only when initial activity levels were very low to normal but plateaued thereafter. We conclude that antithrombin supplementation therapy in patients with sepsis-induced DIC and very low antithrombin activity may improve survival without increasing the risk of bleeding.